Marrow Adipose Tissue: Skeletal Location, Sexual Dimorphism, and Response to Sex Steroid Deficiency - Lecka-Czernik, Beata; Stechschulte, Lance A.; Czernik, Piotr J.; Sherman, Shermel B.; Huang, Shilong; Krings, Amrei (Frontiers in Endocrinology, 2017)
Marrow adipose tissue (MAT) is unique with respect to origin, metabolism, and function. MAT is characterized with high heterogeneity which correlates with skeletal location and bone metabolism. This fat depot is also highly sensitive to various hormonal, environmental, and pharmacologic cues to which it responds with changes in volume and/or metabolic phenotype. We have demonstrated previously that MAT has characteristics of both white (WAT) and brown (BAT)-like or beige adipose tissue, and that beige phenotype is attenuated with aging and in diabetes. Here, we extended our analysis by comparing MAT phenotype in different locations within a tibia bone of mature C57BL/6 mice and with respect to the presence of sex steroids in males and females. We report that MAT juxtaposed to trabecular bone of proximal tibia (pMAT) is characterized by elevated expression of beige fat markers including Ucp1, HoxC9, Prdm16, Tbx1 and Dio2, as compared to MAT located in distal tibia (dMAT). There is also a difference in tissue organization with adipocytes in proximal tibia being dispersed between trabeculae, while adipocytes in distal tibia being densely packed. Higher trabecular bone mass in males correlates with lower pMAT volume and higher expression of beige markers in the same location, as compared to females. However, there is no sexual divergence in the volume and transcriptional profile of dMAT. A removal of ovaries in females resulted in decreased cortical bone mass and increased volume of both pMAT and dMAT, as well as volume of gonadal WAT. Increase in pMAT volume was associated with marked increase in Fabp4 and Adiponectin expression and relative decrease in beige fat gene markers. A removal of testes in males resulted in cortical and trabecular bone loss and the tendency to increased volume of both pMAT and dMAT, despite a loss of gonadal WAT. Orchiectomy did not affect the expression of white and beige adipocyte gene markers. In conclusion, expression profile of beige adipocyte gene markers correlates with skeletal location of active bone remodeling and higher trabecular bone mass, however bone loss resulted from sex steroid deficiency is not proportional to MAT expansion at the same skeletal location.